Analisis Pelayanan dan Pengelolaan Pelabuhan Sri Bintan Pura Tanjungpinang - Ayu Atikhah Adelia; Melza Stefani; Rani Puspita (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2025)
A port is a facility at the end of an ocean, river, or lake to receive ships and move goods and passengers into them. In this function, it means that the port must serve all forms of activities and interests related to the needs of people who will travel by using naval service facilities. Domestic passengers at Sri Bintan Pura port still feel dissatisfied with the service given, such as parking lots that have not been arranged properly, long queuses entering and/or leaving port, passenger terminal waiting room which is still under repair as well as facilities for disabled people who are inadequate. The problem studied is the level of satisfaction passengers (domestic) regarding services at the Sri Bintan Pura port passenger terminal Tanjungpinang. The method used in the research entitled analysis of service and infrasrtucture at the Sri Bintan pura Tanjungpinang port uses a literature riview method with a descriptive approach.